مدى توفر مقومات تطبيق نظام محاسبة المسؤولية في الشركات: دراسة تطبيقية على شركة سرت لإنتاج وتصنيع النفط والغاز - هدي محمد الجدي (Surman Journal of Science and Technology, 2025)
This study aimed to identify the extent to which the requirements for applying the responsibility accounting system are available at Sirte Company for Oil and Gas Production and Manufacturing. These requirements include the identification of responsibility centers within the company, the accounting information system, standard costs and planning budgets, the control reporting system, and the incentive system, to achieve the objectives of the study, the descriptive analytical approach was adopted. The comprehensive survey method was used for the study population, which consisted of employees in the Financial Department and the Internal Audit Department of the company. A total of 76 questionnaires were distributed, of which 73 were retrieved, representing a response rate of 96.05%. Three questionnaires were excluded, bringing the number of questionnaires valid for analysis to 70. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data collected through the study instrument, The study reached several findings, the most important of which is that the requirements for applying the responsibility accounting system are largely available at Sirte Company for Oil and Gas Production and Manufacturing. However, the system of material and moral incentives was available only to a moderate degree, indicating that the company does not have a sufficiently effective system for material and moral incentives ,The study presented a set of recommendations, the most important of which are: raising employees’ awareness of the importance of the responsibility accounting system and the necessity of applying it; using planning budgets as one of the important methods for evaluating performance and comparing actual performance with planned performance; increasing attention to non-financial reports in responsibility centers; and emphasizing the need for top management to give greater importance to the incentive system so that it becomes more effective and fair.